1988
DOI: 10.1055/s-2007-1018122
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Generalized Juvenile Gastrointestinal Polyposis Associated with Gastric Carcinoma

Abstract: A case of generalized juvenile gastrointestinal polyposis associated with gastric adenocarcinoma is described. A 31-year-old male patient developed polyposis of the stomach complicated by gastric carcinoma and multiple polyps in the colon. Polyps of the stomach and colon were pathologically consistent with juvenile polyp, but adenomatous changes were also present in a very small percentage of the juvenile polyps. This case strongly suggests the possibility of carcinoma developing in patients with generalized j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This suggests role in the “multiple” adenoma phenotype [128]. Additionally, there are many reports of patients with juvenile polyposis developing gastrointestinal malignancy, including cancer of the colon [129, 130], stomach [129131], and pancreas [129, 132]. Whether these mutations may directly contribute to the preceding cancers or whether they create a favorable environment that makes a person more susceptible to stomach and colon cancer is not known at this time.…”
Section: Evidence Of Bmp Involvement In Tumorigenesismentioning
confidence: 99%
“…This suggests role in the “multiple” adenoma phenotype [128]. Additionally, there are many reports of patients with juvenile polyposis developing gastrointestinal malignancy, including cancer of the colon [129, 130], stomach [129131], and pancreas [129, 132]. Whether these mutations may directly contribute to the preceding cancers or whether they create a favorable environment that makes a person more susceptible to stomach and colon cancer is not known at this time.…”
Section: Evidence Of Bmp Involvement In Tumorigenesismentioning
confidence: 99%
“…Both siblings underwent a total gastrectomy, and although their stomachs were found to be diffusely involved with typical juvenile polyps, there was no evidence of dysplasia or cancer150. Yoshida et al reported a 31 year old JP patient that was diagnosed with a well-differentiated gastric adenocarcinoma, and concluded that JP patients are also at risk for gastric cancer156. Sassatelli et al reported a 16 year old JP patient with diffuse polyposis of the stomach, who later developed an infiltrating adenocarcinoma from one of the JP polyps in the stomach at the age of 21129.…”
Section: Juvenile Polyposis Syndrome (Jps)mentioning
confidence: 99%
“…Patients with generalized JP should undergo close surveillance of the upper GI tract because of the high risk of malignancy43,55,60,68, Jarvinen, 1984 #570,131,156. Howe et al recommended screening the upper GI tract by EGD starting at the age 15 for asymptomatic individuals at risk, or as soon as signs or symptoms develop.…”
Section: Juvenile Polyposis Syndrome (Jps)mentioning
confidence: 99%
“…[1314] The diagnostic criteria for juvenile polyposis syndrome are somewhat controversial, but we have followed the guidelines outlined by Giardiello et al . [15] Initially, the indications of surgical intervention for JPS were as follows: when polyps are numerous and difficult to control endoscopically, if symptoms such as bleeding and diarrhea are troublesome, or when there is any suspicion of cancer;[1617] however, recently, prophylactic surgical intervention is considered as the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%